HADITS-HADITS PENDIDIKAN (STUDI TAFSIR MAUDHU’) - Hastuti Hastuti; Tasmin Tangngareng (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2024)
This research aims to explore and analyze the hadiths related to education within the context of maudhu' (fabricated) tafsir studies. The research method involves the collection of educational hadiths from various primary sources such as hadith compilations and tafsirs, followed by a critical analysis of their authenticity and relevance in the educational context. The objective of this analysis is to comprehend the educational messages embedded within these hadiths and to assess their practical implications in the modern educational framework. The findings reveal that the educational hadiths examined in the maudhu' tafsir studies contain diverse and relevant values for consideration within the realm of education. There is an emphasis on the significance of learning, teaching, moral values, and ethics in the educational process. Additionally, the analysis highlights the importance of social, cultural, and psychological contexts in understanding the educational messages conveyed in these hadiths. The discoveries from this research contribute to a deeper understanding of the relevance of Islamic educational values found in maudhu' tafsir hadiths and their practical implications in today's educational context. These practical implications encompass the development of teaching methods that integrate ethical and moral values derived from the hadiths, as well as a better comprehension of how Islamic educational principles can be applied within modern educational environments.